2006
DOI: 10.1111/j.1365-3156.2006.01635.x
|View full text |Cite
|
Sign up to set email alerts
|

Stronger host response per parasitized erythrocyte in Plasmodium vivax or ovale than in Plasmodium falciparum malaria

Abstract: Summaryobjective and methods Fever tends to start at a lower level of parasitemia in Plasmodium vivax or ovale than in P. falciparum malaria, but hyperparasitemia and complications are more likely to occur in P. falciparum malaria. Therefore, we compared the relationship between parasitemia and host response parameters before therapy in 97 patients with P. faciparum malaria (18 with complications), and 28 with P. vivax or ovale malaria.results In both types of malaria, parasitemia correlated with blood levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
66
3
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(81 citation statements)
references
References 36 publications
6
66
3
6
Order By: Relevance
“…These changes, which were not identifi ed in the patients infected with P. falciparum, favor a stronger infl ammatory response in severe P. vivax infections that can affect bone marrow via the production of tumor necrosis factor alpha (TNF-α). This hypothesis is supported by a study that identifi ed increased production of TNF-α in P. vivax malaria and a stronger host immune response in P. vivax malaria compared with P. falciparum malaria 48 .…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…These changes, which were not identifi ed in the patients infected with P. falciparum, favor a stronger infl ammatory response in severe P. vivax infections that can affect bone marrow via the production of tumor necrosis factor alpha (TNF-α). This hypothesis is supported by a study that identifi ed increased production of TNF-α in P. vivax malaria and a stronger host immune response in P. vivax malaria compared with P. falciparum malaria 48 .…”
Section: Discussionsupporting
confidence: 63%
“…Our study showed that the patients infected with P. falciparum, but not P. vivax, had more prolonged PTi and PTT when the thrombocytopenia was more severe. This difference may be the result of increased procoagulant activity in P. vivax compared with P. falciparum infections, which develops in response to increased endothelial activity induced by TNF-α levels and the consequent formation of thrombin-antithrombin III 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Severe anaemia was reported in 14.8% (8) cases, which may be due to recurrent bouts of haemolysis and dyserythropoiesis [26]. Besides, in vivax malaria, more number of non-infected RBCs are cleared from the circulation as compared to those in in falciparum malaria [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Cependant, il faut se rappeler que les autopsies sont extrê-mement rares dans les zones de transmission et qu'il n'existe pas de modèle animal vraiment proche du neuro paludisme causé par P. vivax. Le potentiel pro-inflammatoire de vivax semble plus important que celui de falciparum en phase aiguë de la maladie d'après les rares données dont on dispose : une surproduction de TNF (tumor necrosis factor) a été observée 30 à 45 minutes avant l'apparition de la fièvre ; une corrélation entre le niveau sérique d'interleukine 10 (IL-10) et d'IL-12 et la densité parasitaire a été démontrée en Turquie [39]. Que manque-t-il à P. vivax pour être aussi peu délétère malgré une réaction inflammatoire importante ?…”
Section: Mécanismes Physiopathologiques Des Complications Causées Parunclassified